Peningkatan Keterampilan Menulis Jurnal melalui Pendekatan Proses Menulis di Kelas V Sekolah Dasar - Muh. Amin Ali (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2008)
Abstract: The objective of this research was to improve journal writing skills through a writing process approach. The design of the research was action research. The subjects were fifth grade of SDN Sumbersari 3 Malang city. The collected data were analysed by three steps: data reduction, and data description, and conlusion development.The research showed there were some improvements in students related to their journal writing skills.